Dental perspective on Sjögren’s syndrome: literature review - Israel Rodríguez, Jesús; Martínez Sandoval, Gloria; Rodríguez Franco, Norma Idalia; Achapa, María Gabriela; Solís Soto, Juan Manuel (Universidad de Concepción, 2015)
The human body releases around 500-600mL of saliva daily, however when values of unstimulated whole saliva range from 0.1 to 0.2mL/min, there is a condition called Hyposalivation or hyposialia. Hyposalia is characterized by a large number of systemic conditions, including Sjögren’s syndrome, a chronic autoimmune disease that affects between 0.1 and 3% of the world population and is characterized by exocrinopathy of the salivary glands leading to glandular hypofunction and thus decreasing the normal salivary flow. Saliva is part of innate immunity, when there is a decrease in protein secretion, numerous oral manifestations occur such as dental caries, candidiasis, gingival disease, angular cheilitis, lymphomas of the salivary glands, dysphagia, erythematous and fissured tongue, among others. Currently there is no defined dental treatment, however there are alternative treatments by sialogogues and salivary substitutes, plus non-pharmacological therapies, which seek to maintain the ecology and oral conditions stable, in addition to preventive and restorative dental treatment for lesions already established as a consequence of the disease. The aim of this study is to conduct a literature review on the characteristics, classification, oral manifestations and dental management of Sjögren’s syndrome.